A Triazolyl‐Pyridine‐Supported CuI Dimer: Tunable Luminescence and Fabrication of Composite Fibers. Issue 8 (6th July 2015) - Bai, Shi‐Qiang; Kai, Dan; Ke, Karen Lin; Lin, Ming; Jiang, Lu; Jiang, Ying; Young, David James; Loh, Xian Jun; Li, Xu; Hor, T. S. Andy
Abstract: The dinuclear complex [Cu2 I2 (L1)2 ] (1 ) (L1=3‐((4‐(pyridin‐2‐yl)‐1 H ‐1, 2, 3‐triazol‐1‐yl)methyl)benzonitrile) is characterized by single‐crystal X‐ray diffraction (XRD), powder XRD, IR, photoluminescence spectroscopy, and thermogravimetric analysis. Unlike other related, known copper iodide complexes, it exhibits strong yellow emission in the solid state at both room temperature and 77 K. Showing good compatibility with PMMA, it is blended with the polymer in different weight ratios to prepare luminescent composite fibers. Abstract : Glowing results : A strongly emissive copper iodide complex with a hybrid ligand exhibits strong yellow emission in the solid state (see picture). It can be electrospun with poly(methyl methacrylate) to give luminescent composite fibers.